Performance Scrutiny of Nepal Electricity Authority using DuPont Analysis - Risal, Nischal (PYC Nepal Journal of Management, 2019)
The research paper aim to analyze the financial strength and weaknesses of NEA by using DuPont analysis. The descriptive and analytical research designs have been adopted in the research. The quantitative data has been obtained from annual reports of NEA. The study covers eight years period from 2011/12 to 2018/19. The study concludes despite being the sole distributor of the electricity in the country, the financial performance, measured in terms of ROE, of NEA is very poor in first five years (2010/11 – 2015/16) of the study period. The primary source of such poor performance was negative profit margin. Besides, NEA is also exposed to higher financial risk measured in terms of equity multiplier. However, both these measures, ROE and EM have improved in later two years (2016/17 – 2017/18) of the study period.